Hidden Greens- A Preliminary Checklist of Bryophytes From Adampur Forest, Sylhet (Bioresearch Communications, 2026)
Bryophytes, though ecologically important, remain underrepresented in biodiversity research across South Asia. This study documents the bryophyte diversity of Adampur Forest in Moulvibazar, Sylhet, an area rich in microhabitats but previously unexplored for non-vascular flora. A field survey yielded more than 20 specimens, of which 20 species were identified and recorded with photographic documentation. These results constitute the first documented photographic record of bryophytes from this forest and provide a dependable baseline for future taxonomic and ecological research. Beyond contributing to species identification, the work highlights the ecological significance of bryophytes and underscores the need for broader surveys across seasons and regions. By raising awareness of overlooked components of forest ecosystems, this study supports biodiversity monitoring and conservation efforts in Bangladesh.Bioresearch Commu. 12(1): 2086-2090, 2026 (January)